2021
DOI: 10.1186/s40478-021-01191-w
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the vulnerability of mice expressing human superoxide dismutase 1 to prion-like seeding: a study of the influence of primary amino acid sequence

Abstract: Misfolded forms of superoxide dismutase 1 (SOD1) with mutations associated with familial amyotrophic lateral sclerosis (fALS) exhibit prion characteristics, including the ability to act as seeds to accelerate motor neuron disease in mouse models. A key feature of infectious prion seeding is that the efficiency of transmission is governed by the primary sequence of prion protein (PrP). Isologous seeding, where the sequence of the PrP in the seed matches that of the host, is generally much more efficient than wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 62 publications
(148 reference statements)
2
15
0
Order By: Relevance
“… 168 In contrast with other prion-like pathogenic proteins found in Alzheimer’s disease or Parkinson’s disease, no evidence of an ALS pathology supported by wildtype human SOD1 spread have been revealed. 169 Indeed, recent work reveals that transgenic mice overexpressing wildtype SOD1 appear to be resistant to misfolded mutant SOD1 seeds. 169 Together, these results show that mutant SOD1 aggregates can transmit and propagate ALS-like dysfunctions when they reach the CNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 168 In contrast with other prion-like pathogenic proteins found in Alzheimer’s disease or Parkinson’s disease, no evidence of an ALS pathology supported by wildtype human SOD1 spread have been revealed. 169 Indeed, recent work reveals that transgenic mice overexpressing wildtype SOD1 appear to be resistant to misfolded mutant SOD1 seeds. 169 Together, these results show that mutant SOD1 aggregates can transmit and propagate ALS-like dysfunctions when they reach the CNS.…”
Section: Introductionmentioning
confidence: 99%
“… 169 Indeed, recent work reveals that transgenic mice overexpressing wildtype SOD1 appear to be resistant to misfolded mutant SOD1 seeds. 169 Together, these results show that mutant SOD1 aggregates can transmit and propagate ALS-like dysfunctions when they reach the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The method used for sciatic nerve injections has been described in detail previously [ 13 , 22 ], with the following modification. To reduce postoperative pain, after the injection site was shaved and sterilized, the site was injected subcutaneously with 100 ul of a 0.05% solution of bupivacaine.…”
Section: Methodsmentioning
confidence: 99%
“…We have extensively used a version of G85R-SOD1 mice in which the human protein is fused in frame to yellow fluorescent protein (YFP) [ 21 ]. Mice that are heterozygous for the transgene do not develop paralysis until after 18 months of age [ 21 , 22 ], whereas newborn mice injected with preparations containing misfolded SOD1 conformers develop paralysis in less than 3 months [ 18 , 22 ]. Additionally, we observed that injecting fibrilized recombinant human SOD1 can induce early-onset paralysis in G85R-SOD1:YFP mice [ 14 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation